Students’ readiness to teaching practice experience: A review from the mathematics education students' view - Heri Retnawati; Eny Sulistyaningsih; Lau Yoke Yin (Jurnal Riset Pendidikan Matematika, 2018)
A teaching practice is an effort to improve prospective teachers’ competence. Students’ development in the teaching practice is the key to its successful implementation. This study aims at describing and gaining an understanding of readiness of mathematics education students in conducting teaching practices. This study is a qualitative research with a type of phenomenology. Data were obtained from an open questionnaire of students from Indonesia and Malaysia. The participants of this study were 23 seventh semester students who have implemented teaching practices for 2 months. Data were analyzed using Bogdan Biklen approach. The result revealed that students’ ability in conducting the teaching practice was good, but they still need to improve managing the classroom. The constraints experienced by the teachers were related to learning instructions and time allocations, while for the students, the learning equipment facilities, coordination, school policy, and culture became their problems. However, both students and teachers had their own various strategies in overcoming these obstacles.